O financiamento da política estadual de assistência social (Espírito Santo, 2004-2015) - Martins, Bruna de Andrade (2018)
This dissertation analyzed the financial management of the State Social Welfare Policy of the State of Espírito Santo, from 2004 to 2015, in order to understand and problematize how the state sphere of action in this social policy was characterized. To do so, our methodological path brought together bibliographic, documentary and field research. We conducted interviews with subjects directly involved in the budget dynamics of social assistance, whether acting in the technical and administrative areas of the managing body or in social control. This study, which is based on dialectical historical materialism, discusses the role of the State in late capitalism; the capture of the public fund by countercyclical strategies; of the fiscal crisis and its refutations in the federative pact and in the financing of Brazilian social security. After embarking on the State public budget, we present the magnitude, amount and direction of social spending with social assistance in Espírito Santo. The analysis revealed the state government's choices over twelve years (2004 to 2015) and what direction the public fund was given in this context. The research indicated that the socio-welfare protection of the capixabas was not the priority of the state government, this indicative has as its mainstay the residual place that the expenditures with the State Policy of Social Assistance had on the state budget. In addition to insufficient allocation of resources, this social policy was hampered by budget cuts; misappropriation of resources through a parallel fund to the FEAS and budget actions that do not correspond to the content, principles and guidelines of SUAS; and the non-implementation of the budget for assistance in its entirety. The state government's role in social assistance was predominantly through transitional and selective government programs, targeted income transfers, and emphasis on co financing of basic social protection, with difficulty in expanding special social protection. The absence of the state plan is an essential gap identified in SUAS do Espírito Santo, which reflected directly in the dispersion of resources that should have been applied in services regularly classified as social assistance, but were destined to other areas and actions other than social assistance